Cultural awareness (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. In this track, we'll discuss cultural awareness, and discover how being culturally aware enables us to communicate with people more effectively, as well as to respond to and interact with the cultures of others. Learning Objectives Learn what it means to be culturally aware Learn new ways to show cultural sensitivity.